2014
DOI: 10.3892/ijo.2014.2691
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs drive metastatic progression in melanoma (Review)

Abstract: Abstract. Metastatic melanoma is the leading cause of skin-cancer related deaths and while in recent years some progress has been made with targeted therapies, there remains an urgent unmet need for novel therapeutic treatments and reliable diagnostic, prognostic and predictive biomarkers. the emergence of next generation sequencing (ngS) has seen a growing appreciation for the role played by non-coding genomic transcripts in regulating gene expression and by extension impacting on disease progression. the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…These non‐protein‐coding transcripts (longer than 200 nucleotides) were shown to be implicated in tumorigenesis; however, their functions and downstream mechanisms are still largely unknown. As summarized in a recent review (Akhbari et al., ), HOTAIR expression is dramatically upregulated in metastatic versus primary melanoma (Tang et al., ). This upregulation leads to increased transcription of the metalloproteinases MMP2 and MMP9, which favor metastatic spread.…”
Section: Micrornas In Melanoma and Melanoma‐subtype‐specific Micrornasmentioning
confidence: 99%
“…These non‐protein‐coding transcripts (longer than 200 nucleotides) were shown to be implicated in tumorigenesis; however, their functions and downstream mechanisms are still largely unknown. As summarized in a recent review (Akhbari et al., ), HOTAIR expression is dramatically upregulated in metastatic versus primary melanoma (Tang et al., ). This upregulation leads to increased transcription of the metalloproteinases MMP2 and MMP9, which favor metastatic spread.…”
Section: Micrornas In Melanoma and Melanoma‐subtype‐specific Micrornasmentioning
confidence: 99%
“…Overexpression of BANCR in MM promotes the activation of the extracellular signal-regulated kinases 1/2 (ERK1/2) and c-Jun N-terminal kinase (JNK) components of the MAPK pathway, while its knockdown affects the migratory capacity of tumour cells [ 75 , 76 ]. A positive feedback mechanism with the V600E mutation is thought to induce BANCR overexpression, subsequent upregulation of chemokines and increase in melanoma cell motility [ 76 , 77 ].…”
Section: Lncrnas Modulate Melanoma Invasion and Metastasismentioning
confidence: 99%
“…A positive feedback mechanism with the V600E mutation is thought to induce BANCR overexpression, subsequent upregulation of chemokines and increase in melanoma cell motility [76,77].…”
Section: Lncrnas Modulate Melanoma Invasion and Metastasismentioning
confidence: 99%
“…[41, 42] Others have suggested that SPRY4-IT1 manipulates the RAS/ERK pathway given its membership of the Sprouty family of RAS/ERK inhibitor proteins that prevent the formation of active GTP-RAS. [43] However, these hypotheses still need to be confirmed experimentally.…”
Section: Identification Of Lncrnas In Cutaneous Melanoma and Their Momentioning
confidence: 99%